1992
DOI: 10.1042/bj2880341
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E in human low-density lipoprotein. When and how this antioxidant becomes a pro-oxidant

Abstract: Uptake of oxidatively modified low-density lipoprotein (LDL) by cells in the arterial wall is believed to be an important early event in the development of atherosclerosis. Because vitamin E is the major antioxidant present in human lipoproteins, it has received much attention as a suppressor of LDL lipid oxidation and as an epidemiological marker for ischaemic heart disease. However, a careful examination of lipid peroxidation in LDL induced by a steady flux of aqueous peroxyl radicals has demonstrated that, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
258
2
2

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 478 publications
(279 citation statements)
references
References 13 publications
14
258
2
2
Order By: Relevance
“…Previous studies from this laboratory [12,15] (J. Neuzil, S.R. Thomas and R.S., unpublished) have demonstrated that the extent to which the pro-oxidant activity of ~-TOH in ascorbateand ubiquinol-10-free LDL is seen depends largely on the rate of peroxidation initiation (Ri) rather than the nature of the ~-TOH and Chl8:2-OOH (squares) were determined as described [21].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies from this laboratory [12,15] (J. Neuzil, S.R. Thomas and R.S., unpublished) have demonstrated that the extent to which the pro-oxidant activity of ~-TOH in ascorbateand ubiquinol-10-free LDL is seen depends largely on the rate of peroxidation initiation (Ri) rather than the nature of the ~-TOH and Chl8:2-OOH (squares) were determined as described [21].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, since α-tocopherol is an efficient Cu(II) reductant [14,30] and during this reaction it is rapidly consumed [34], the shift of the copper redox equilibrium toward Cu(I) would spare endogenous α-tocopherol and would make LDL more resistant to an oxidative attack. Additionally, it can be proposed that uric acid might act in synergism with α-tocopherol by reducing tocopheroxyl radical back to the parent compound.…”
Section: Discussionmentioning
confidence: 99%
“…In a number of very elegant studies Stocker and co-workers [14][15][16] have demonstrated that the antioxidant α-tocopherol may behave, under appropriate conditions, as pro-oxidant, thus paradoxically stimulating LDL oxidation promoted by a constant radical flow originating from the thermal decomposition of the azo-compound 2,2h-azobis-(2-amidino propane) hydrochloride (AAPH) or by low concentrations of copper. The pro-oxidant activity of α-tocopherol is mediated through the one-electron oxidation catalysed by peroxyl radicals or by the reductive activation of Cu(II) to Cu(I) with the concomitant formation of the α-tocopheroxyl radical which, in turn, may abstract a hydrogen atom from a polyunsaturated fatty acid in LDL, thus initiating a radical chain ultimately leading to extensive lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the epidemiological evidence indicating an inverse relationship between dietary fruit and vegetable intake and the incidence of cardiovascular disease [20,21], numerous studies have been undertaken to show that micronutrients provided by such diets, including α-tocopherol [22,23], ascorbic acid [24][25][26][27] and various flavonoids [28][29][30][31], can protect LDL from oxidative modification [32]. Under certain circumstances, however, they have been shown to display prooxidant activity.…”
Section: Introductionmentioning
confidence: 99%
“…Under certain circumstances, however, they have been shown to display prooxidant activity. Indeed, it has been suggested the α-tocopheroxyl radical, generated by the oxidation of α-tocopherol within LDL, is the species responsible for the initiation of lipid peroxidation in the particle [22,33,34].…”
Section: Introductionmentioning
confidence: 99%